2017
DOI: 10.14814/phy2.13050
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 and ET receptors impair left ventricular function by mediated coronary arteries dysfunction in chronic intermittent hypoxia rats

Abstract: Obstructive sleep apnea (OSA) results in cardiac dysfunction and vascular endothelium injury. Chronic intermittent hypoxia (CIH), the main characteristic of OSAS, is considered to be mainly responsible for cardiovascular system impairment. This study is aimed to evaluate the role of endothelin‐1(ET‐1) system in coronary injury and cardiac dysfunction in CIH rats. In our study, Sprague–Dawley rats were exposed to CIH (FiO2 9% for 1.5 min, repeated every 3 min for 8 h/d, 7 days/week for 3 weeks). After 3 weeks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…At 4 months of age, ET-1 tissue levels were increased in coronary arteries from prenatal hypoxia females only, while ET-1-mediated vasoconstriction and plasma levels of ET-1 were not affected by prenatal hypoxia in either sex. Previous research in an adult rat model of chronic intermittent hypoxia reported an enhanced ET-1 expression in coronary vessels that was accompanied with an enhanced ET-1-mediated response [ 63 ]. Thus, it can be suggested that prenatal hypoxia may have an adaptive response in that, although there was an increase in ET-1 expression, this was not accompanied by an increased ET-1-mediated coronary artery responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…At 4 months of age, ET-1 tissue levels were increased in coronary arteries from prenatal hypoxia females only, while ET-1-mediated vasoconstriction and plasma levels of ET-1 were not affected by prenatal hypoxia in either sex. Previous research in an adult rat model of chronic intermittent hypoxia reported an enhanced ET-1 expression in coronary vessels that was accompanied with an enhanced ET-1-mediated response [ 63 ]. Thus, it can be suggested that prenatal hypoxia may have an adaptive response in that, although there was an increase in ET-1 expression, this was not accompanied by an increased ET-1-mediated coronary artery responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Both hypoxia-inducible factors (HIF) 1 and 2 and NF-B respond to IH by modulating the oxidative stress and inflammatory pathways and cell apoptosis in endothelial cells (26,53). Moreover, IH elicits changes in the gene expression and secretion of proinflammatory cytokines (51) and adipokines (27), affects nitric oxide coupling (6), and endothelin-1 and endothelin receptors (69), and increases the circulating levels of vascular endothelial growth factor (2), which has been shown to be implicated in endothelial wound healing with serum of OSA patients (10). In this context of IH, it could be possible that the response of each cell to a time-varying environment could involve slowand fast-response mechanisms, which would be mainly driven by the average hypoxia throughout the cycle and by the rate and magnitude of hypoxic cycling, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…ET produced by endothelial cells and other cell types is one of the most investigated molecules among vascular biology, which functions as an effective endothelium‐derived vasoconstrictor and may participate in mechanisms leading to hypertension . ET‐1 is one of the three isoforms of ET that functions as a powerful vasoconstrictor produced by the vascular endothelium cells and plays a significant role in the cardiovascular changes . Endothelins bind to ETRs to initiate their downstream effects.…”
Section: Discussionmentioning
confidence: 99%